2020
DOI: 10.2174/1570179417666200226092516
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of Poly Heterocyclic Compounds Containing [1,2,4]triazolo and [1,2,3,4]tetrazolo Moieties and their DFT Study as Expected Anti-cancer Reagents

Abstract: Background: 2-amino-3-cyanopyridines are good starting reagents that have been used in synthesis of many heterocyclic compounds such as pyridopyrimidines, [1,2,4]triazolo and [1,2,3,4] tetrazolo derivatives which have biological activities as anti-microbial and cytotoxic activities. Meanwhile [1,2,4]triazolo and [1,2,3,4]tetrazolo derivatives are well known to possess many physiological activities, such as anticancer , antifungal, muscle relaxant, hypnotic, anti-inflammatory, diuretic and antihypertensive acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…1 b-i), but no change in the maximum emission wavelength of HPf was observed. This observation could be attributed to the high affinity of Cu 2+ ions to the carbonyl and carboxylic groups present in the pefloxacin molecule as a ligand [ 53 ] and that the ion can strongly quench the inner fluorescence of the pefloxacin ligand and that the interaction between the bioligand and metal ion indeed existed without inducing any conformational change in pefloxacin. Static quenching implies either the existence of a sphere of effective quenching or the formation of a ground state nonfluorescent complex.…”
Section: Resultsmentioning
confidence: 99%
“…1 b-i), but no change in the maximum emission wavelength of HPf was observed. This observation could be attributed to the high affinity of Cu 2+ ions to the carbonyl and carboxylic groups present in the pefloxacin molecule as a ligand [ 53 ] and that the ion can strongly quench the inner fluorescence of the pefloxacin ligand and that the interaction between the bioligand and metal ion indeed existed without inducing any conformational change in pefloxacin. Static quenching implies either the existence of a sphere of effective quenching or the formation of a ground state nonfluorescent complex.…”
Section: Resultsmentioning
confidence: 99%
“…Gas chromatography and spectroscopy are commonly used to determine the crystal structure of separated chemical components. [22,23] In order to fully apply the database to save research costs and reflect the role of computer technology in drug research and development, the molecular structure of 6-Gingerol (PubChem CID: 442793) and nuciferin (PubChem CID: 10146) was selected from the public chemistry database (PubChem), converted into a three-dimensional structure with ChemBio3D Ultra12.0, [24] and optimized using the MMFF94 force field (Hagler, 1996). To evaluate the interaction mode of 6-Gingerol and Nuciferin with SLC6A2 (Sodium-dependent noradrenaline transporter), SLC6A3 (Sodium-dependent dopamine transporter), and SLC6A4 (Sodium-dependent serotonin transporter) proteins, AutoDock Vina 1.1.2 [25] was used.…”
Section: Methodsmentioning
confidence: 99%
“…As we mentioned in our recent articles, triazolo compounds and particular [1,2,4]­triazolo derivatives are well known to have many physiological activities, such as anticancer. , Also, [1,2,4]­triazole derivatives have been reported as antimicrobial, insecticidal, fungicidal, antidepressant, hypnotic, anti-inflammatory, antihypertensive, and plant growth regulator. On the other hand, 1,3,4-oxadiazole has become an essential building unit for the creation of new drugs where a literature survey showed that a slight systemic change in 1,3,4-oxadiazole moiety structure could lead to qualitative as well as quantitative changes in 1,3,4-oxadiazole derivative activity, which convinced us to start synthesizing different new 1,3,4-oxadiazole derivatives in order to increase their activity and lower their toxicity. Over the last 2 decades, the synthesis of novel 1,3,4-oxadiazole derivatives and the investigation into their chemical properties and biological behavior have increased. Also, the combination of oxadiazole and other heterocycles such as pyrrole and pyrazole rings in one compound led to several biological activities of these compounds. We may therefore conclude that 1,3,4-oxadiazole is one of the main pharmacophores that plays an important role in pharmaceutical chemistry and has a broad range of important biological activities including anti-inflammatory, , anticancer, antimalarial, antibacterial, anticonvulsant, antitubercular, anti-allergic agent, analgesic, and vasodilator .…”
Section: Introductionmentioning
confidence: 99%